Development of an Electron-Transporting π-Conjugated Polymer Containing Fluorine-substituted Naphthobisthiadiazole - Ie, Yutaka; Izuno, Kakeru; Moriyama, Taichi; Aso, Yoshio (Journal of Photopolymer Science and Technology, 2019)
The development of new organic semiconductors for organic solar cell applications continues to be as an important subject. We recently developed fluorinated naphthobisthiadiazole (FNTz) for use as a new electron-accepting unit for nonfullerene acceptors. In this letter we report on the design and synthesis of a new electron-transporting π-conjugated polymer containing FNTz and an investigation of the influence of the FNTz unit on the properties and photovoltaic characteristics of the molecule. The introduction of the FNTz unit led to red-shifted absorption and low-lying frontier orbital energy levels, compared to those of NTz. Organic solar cells based on the FNTz–containing polymer, when combined with poly(3-hexylthiophene) as a donor showed an improved power conversion efficiency of 1.13%. These results indicate that FNTz could be an effective electron-accepting unit for electron-transporting polymer.